The Character Strengths Response: An Urgent Call to Action - Mayerson, Neal H. (Frontiers in Psychology, 2020)
A model on the role of character strengths in individual, collective, and species success is proffered. It is derived from viewing character strengths from an evolutionary perspective as opposed to one of individual psychology. The history of the VIA initiative on character science is overviewed, and results to date are summarized in terms of promoting well-being, helping to accomplish aspirational intentions, and allowing the greater good of the collective to grow. “The character strengths response” is described as the response capacities that character strengths enable for helping us fulfill the human promise of surviving, thriving, and successfully creating a next-generation so that individuals and the collective flourish while also living in harmonious balance with other species. An argument is presented that there is an urgent need for advancing population-wide psychological maturity to be better prepared to navigate the difficult decisions that accompany growing technological powers, and that the character strengths response warrants special attention of research funding to accomplish this imperative.